(3GdLhGgQ GdMSGf hTeS Yjf GdReGf aj Yde GdbHGfs - (3GdbHGfj , NVQ Hf YHO GdQMef Hf CMeO Hf Ydj GdHQdSj,J (B853 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi RGf ef faSg HGdYde RGFf s
(3BNQgG (B:s
(3hGddg JYGdi fGaP HUjQ, hgh Gdehab Hefg hcQeg s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B307s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjVjGJ (B- (3bSe (B3 - (3U (B40 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs